2015
DOI: 10.15376/biores.10.2.2836-2849
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Methylene Blue from Aqueous Solution using Porous Biochar Obtained by KOH Activation of Peanut Shell Biochar

Abstract: aBiochar from peanut shell was used as the precursor for the preparation of porous biochar by KOH activation. The pore structures of porous biochar also were characterized by scanning electron microscopy (SEM) and N2 adsorption/desorption. The adsorption performance for the removal of methylene blue (MB) was deeply investigated. The effects of impregnation ratio (KOH/biochar: w/w), activation temperature, and activation time on the removal of methylene blue by porous biochar were evaluated. In addition, the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(15 citation statements)
references
References 26 publications
2
12
0
Order By: Relevance
“…A comparison of the R 2 values suggests in table 4 that experimental data fitted well into pseudo-second order adsorption process. This trend has been reported by other researchers who have worked with similar bio-based adsorbents (Han et al, 2015;Tan et al, 2016).…”
Section: Kinetic Studiessupporting
confidence: 85%
“…A comparison of the R 2 values suggests in table 4 that experimental data fitted well into pseudo-second order adsorption process. This trend has been reported by other researchers who have worked with similar bio-based adsorbents (Han et al, 2015;Tan et al, 2016).…”
Section: Kinetic Studiessupporting
confidence: 85%
“…Thus, the Mg-biochar can be used as an efficient adsorbent for humate removal at relatively higher pH values. Han et al (2015) also found KOH activated peanut shell biochar could effectively remove organic pollutants from aqueous solutions. Obviously, the ammonium adsorption capacity was increased when the pH rose to 7.0 and remained more or less constant (~21 mg/g) at pH 7.0 -8.5, suggesting that ammonium was responding to the diminishing positively charged Mg-biochar surface.…”
Section: Effect Of Solution Ph and Coexisting Substances On Adsorptionmentioning
confidence: 92%
“…All of these works [41,42,43,44,45,46,47,48,49,50] concluded that K2 better described the experimental kinetic data, except in ref. [49] in which K1 gave a better fit in the case of As(V) adsorption (while K2 was more satisfactory in the case of Cr(III) and Cr(VI)).…”
Section: Data Reported In 2015mentioning
confidence: 99%
“…Among these publications 4 could not be used because all of the data were at equilibrium [41,42,43,44]. As a consequence, these studies unsurprisingly reported better performance of K2 over K1 as noted in section 3.1.…”
Section: Data Reported In 2015mentioning
confidence: 99%